Validasi Metode Analisis Multiresidu Pestisida Organoklor dalam Salak Menggunakan Kromatografi Gas-Detektor Penangkap Elektron - Tri Joko Raharjo; Bambang Sutriyanto; Mai Anugrahwati; Nurul Hidayat Aprilita (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
Validation of methods is a key step in the accreditation process of the method. Validation of organoklor pesticide residues method in snakefruit based on the method recommended by FAO-WHO, conducted in LPPT-UGM reported in this study. Snake fruit was homogenized, extracted using toluene/2-propanol (2:1), cleaned up using activated carbon and Celite 545, followed by analysis using gas chromatography-electron capture detector. Validation covered specificity and selectivity, limits of detection and quantification, linear range, precision and accuracy. Validation results showed good specificity and selectivity shown by the inter-peak chromatogram resolution greater than 1.5. Limits of detection and quantification for heptaklor, endosulfan, dieldrin and p, p-DDT were 0.002 and 0.006, 0.5 and 1.7; 0.0006 and 0.002, as well as 0.014 and 0.047 ppm respectively. The linear range for heptaklor, endosulfan, dieldrin, and p,p-DDT were 0.0017 to 2 ppm, 0.165 to 2 ppm, 0.023 to 2 ppm and 0.229 to 2 ppm, respectively. Precision methods meet the acceptance of Horwitz RSD value less than 12.78% at a concentration of 0.3 ppm. Accuracy is indicated by recovery, for each pesticide in the range of 80-110% acceptance at a concentration of 0.1 ppm. Analysis of organochlorine pesticides in three commercial snakefruit samples showed no pesticide residues at concentrations higher than the detection limit.ASBTRAKValidasi metode merupakan tahap kunci dalam proses akreditasi suatu metode. Validasi metode uji residu pestisida organoklor dalam salak berdasarkan metode yang direkomendasikan FAO-WHO, di LPPT-UGM dilaporkan pada penelitian ini. Buah salak dihomogenisasi, diekstraksi menggunakan toluen/2-propanol (2:1), clean up menggunakan karbon aktif dan Celite 545, dilanjutkan analisis menggunakan kromatografi gas-detektor penangkap elektron. Validasi mencakup spesifisitas dan selektivitas, batas deteksi dan kuantifikasi, range linier, presisi serta akurasi. Hasil validasi menunjukkan spesifisitas dan selektivitas yang baik ditunjukkan dengan resolusi antar puncak kromatogram lebih besar dari 1,5. Batas deteksi dan batas kuantifikasi untuk heptaklor, endosulfan, dieldrin dan p,p-DDT secara berturut-turut adalah 0,002 dan 0,006; 0,5 dan 1,7; 0,0006 dan 0,002; serta 0,014 dan 0,047 ppm. Range linier untuk heptaklor adalah 0,0017-2 ppm, endosulfan 0,165-2 ppm, dieldrin 0,023-2 ppm dan p,p-DDT 0,229-2 ppm. Presisi metode memenuhi batas keberterimaan Horwitz dengan nilai RSD lebih kecil dari 12,78% pada konsentrasi 0,3 ppm. Akurasi ditunjukkan dengan recovery, untuk tiap pestisida masuk dalam rentang keberterimaan 80-110% pada konsentrasi 0,1 ppm. Analisis pestisida organoklorin pada 3 sampel salak komersial menunjukkan tidak adanya residu pestisida dengan konsentrasi lebih tinggi dari batas deteksi.